Information Technology Governance Domains in Hospitals: A Case Study in Iran - Shahi, Mehraban (Glob J Health Sci, 2015)
IT governance is a set of organizational structures ensuring decision-making rights and responsibilities with regard to the organization’s IT assets. This qualitative study was carried out to identify the IT governance domains in teaching hospitals affiliated to Iran University of Medical Sciences. There were 10 heads of IT departments and 10 hospital directors. Semi structured interviews used for data collection. To analyze the data content analysis was applied. All the interviewees (100%) believed that decisions upon hospital software needs could be made in a decentralized fashion by the IT department of the university. Most of the interviewees (90%) believed that there were policies for logistics and maintenance of networks, purchase and maintenance, standards and general policies in the direction of the policies of the ministry of health and medical education. About 80% of the interviewees believed that the current emphasis of the hospital’s IT unit and the hospital management for outsourcing of services were in the format of specialized contracts and under supervision of the university Statistic and IT department. A hospital strategic committee is an official organizational group consisting of hospital executives, heads of IT and multiple functional areas and business units in a hospital. In this committee, “the head of hospital” acts as the director of IT activities and ensures that IT strategies are alignment with the hospital business strategies.